DIABETIC TRACTIONAL RETINAL DETACHMENT REPAIR BY VITREORETINAL FELLOWS IN A COUNTY HEALTH SYSTEM. Issue 2 (February 2015) - Rahimy, Ehsan; Pitcher, John D.; Gee, Christopher J.; Kreiger, Allan E.; Schwartz, Steven D.; Hubschman, Jean-Pierre
Abstract : Purpose: To investigate anatomical and functional outcomes of vitreoretinal fellow-performed vitrectomy for tractional retinal detachment secondary to proliferative diabetic retinopathy in a county hospital system. Methods: Consecutive retrospective review of patients surgically treated for diabetic tractional retinal detachment at Olive View-UCLA County Medical Center (Sylmar, CA) during a 2-year training period. Results: Sixty-two eyes of 58 patients met inclusion criteria with a mean age of 48 ± 9 years and preoperative hemoglobin A1c of 8.4 ± 1.9%. Previous panretinal photocoagulation had been performed in 34 eyes (54.8%). Mean surgery duration was 153 ± 54 minutes. There was no significant time difference observed between first-year fellow surgeries (159.5 ± 52.3 minutes) and those performed by second-year fellows (146.8 ± 56.4 minutes, P = 0.35), although there was a trend toward longer first-year surgical times. After a mean follow-up of 11.2 months, successful retinal reattachment was achieved in 56 eyes (90.3%). Overall, mean logMAR visual acuity improved from 2.0 ± 0.5 to 1.4 ± 0.8 ( P = 0.0007). Final visual acuity had improved in 33 eyes (53.2%), was unchanged in 11 eyes (17.7%), and decreased in 18 eyes (29%). Postoperative complications encountered included early vitreous hemorrhage in 10 eyes (16.1%), delayed vitreous hemorrhage in 3 eyes (4.8%), secondary rhegmatogenous retinal detachment in 11 eyes (17.7%), and neovascular glaucoma in 5 eyes (8%). Second-year fellows had a lower incidence of rhegmatogenous retinal detachment than first-year fellows ( P = 0.016). Conclusion: Patients with diabetic tractional retinal detachment present to county hospitals with more complex retinal pathology, yet surgical outcomes as performed by vitreoretinal fellows compare favorably to previously reported series. Abstract : Patients with diabetic tractional retinal detachment present to county hospitals with complex retinal pathology, yet surgical outcomes as performed by vitreoretinal fellows compare favorably to previously reported series. Given the increasing interest in the quality of surgical training offered by vitreoretinal fellowship programs, this study, as well as our institution's educational model, may serve as a reference point for future endeavors.